The relationship between temperament and cognitive flexibility in infants - Lee, Janice Jia Yi (Nanyang Technological University, 2021)
Existing literature suggests that temperament, a genetic and behavioural construct of an individual’s emotional reactivity, is related to executive function in information processing and decision making. Of particular interest is an executive function called cognitive flexibility, which requires flexible mental shifting between multiple goals and perspectives. While cognitive flexibility is widely studied in children and adults, it is not well-researched in infants. This study investigates the relationship between temperament and cognitive flexibility in infants. 28 infants completed the A-not-B task which measures cognitive flexibility via finding a toy that switches in hiding location. Infants were rated on temperament scales of surgency, negative affect and effortful control. Partial correlations controlling for age and correcting for Type 1 error showed nonsignificant correlations between all temperament scales and cognitive flexibility. The results did not support the hypothesis that temperament and cognitive flexibility are related constructs. Potential reasons for nonsignificance include low power, random response, methodological differences and individual differences in motivation among infants.